Biodiversity accounts for the butterflies of the Australian Capital Territory. Issue 2 (27th December 2022) - Bond, Suzi; Vardon, Michael
Abstract: Biodiversity accounting is promoted as a way of improving the conservation of species and ecosystems. Advancing the theory and practice of biodiversity accounting is driven by the United Nation's standardization of ecosystem accounting in 2021 and a desire to make production of ecosystem accounts commonplace and useful. While the theory of biodiversity accounting has advanced, in practice few accounts have been produced and all have focused on iconic or threatened species. We present a set of novel biodiversity accounts for the 92 butterfly species of the Australian Capital Territory (ACT), spanning 1978–2021, using historical records and systematic surveys of 224 sites between 2014–15 and 2020–21 in the Southern Hemisphere survey season (Spring‐Autum). We conclude that species level biodiversity accounting is useful for biodiversity conservation and that species accounting must go beyond accounting for iconic and threatened species and reflect other characteristics, such as the distribution, abundance, residential status, breeding status, endemism, and ecological status of all species. Habitat specialization provides a link to ecosystem condition accounting, with changes in the distribution and abundance of habitat specialists a likely indicator of ecosystem condition. With such information, species accounts can be used to assess and target conservation activity and examples for ACT butterflies are provided. Abstract : Biodiversity accounting is a way of organizing information to improve the conservation of species and ecosystems. We present butterfly accounts for the Australian Capital Territory, Australia, covering 92 species and spanning the years 1978–2021. We conclude that to be useful for biodiversity conservation, biodiversity accounting must the reflect the distribution, abundance, residence, breeding status, endemism, and habitat specialization of all species, and not just iconic or endangered species.